PENGARUH BRAND IMAGE DAN SERVICE QUALITY TERHADAP KEPUASAN PELANGGAN, SERTA IMPLIKASINYA PADA WORD OF MOUTH STUDI KASUS PADA UNIVERSITAS MERCU BUANA JAKARTA - Prastowo, Sugeng Lubar (EKONOMI BISNIS, 2018)
The condition of the number of universities that very much as well as the changing demands of consumers and potential consumers of the attributes and performance of educational services that they get trigger increased intensity of competition among service providers colleges. Evident of instability number ratio of new admissions process at UMB. This study aims to examine and analyze the effect of brand image, service quality to customer satisfaction as well as its implications on word of mouth at the University of Mercu Buanan Jakarta. The research data is taken from the questionnaire data of 100 students, the results of the calculation formula of slovin with error or error rate of 10% = 0. The sampling method that has been used is convenience sampling of 6947 the population of regular students at UMB. The analysis method that has been used in this research is the Structural Equation Modeling (SEM). Research shows that brand image, service quality and customer satisfaction significantly influence word of mouth. Partially showed that the brand image factors certainly has a positive and significant impact on customer satisfaction, service quality factors are also has a positive and significant impact on customer satisfaction, and customer satisfication factor also has a positive and significant impact on word of mouth. Service quality is the most powerful variable influence on customer satisfaction in Mercu Buana University.